2014
DOI: 10.11622/smedj.2013190
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent and persistent pityriasis rosea: an atypical case presentation

Abstract: It is a common, acute, selflimiting papulosquamous eruption that is characterised by oval erythematous squamous lesions of the trunk and limbs, usually sparing the face, scalp, palms and soles.(1) Typically, the disease begins with a solitary patch termed a 'herald patch', after which generalised eruption appears along Langer's lines of cleavage. The herald patch has been observed in over 50% of patients, and multiple herald patches have also been reported.Up to 69% of patients have a prodromal illness before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…A herald patch was not detected in relapses, the number and size of the lesions decreased and the duration was shorter compared to the primary disease (15). In a 24-year-old man, Chuah et al (18) observed 3 attacks, each manifesting with a herald patch, but the form and severity of the lesions were milder compared to the primary disease. In contrast, Zawar & Kumar.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A herald patch was not detected in relapses, the number and size of the lesions decreased and the duration was shorter compared to the primary disease (15). In a 24-year-old man, Chuah et al (18) observed 3 attacks, each manifesting with a herald patch, but the form and severity of the lesions were milder compared to the primary disease. In contrast, Zawar & Kumar.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, after the primary episode, the earliest and latest recurrence cases were reported to be two weeks (18) and two years (20), respectively. In the current study, the earliest recurrence occurred after 3 weeks and the latest after 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…PR usually lasts 6-8 weeks, although durations as short as 2 weeks have also been reported. A persistent form of PR (PPR) has been reported only in 1 patient so far [7]. Here, we report on 12 patients in whom the clinical and virological features of PR lasted longer than 12 weeks, suggesting that, as in the case of relapsing PR [8], PPR is another atypical form of PR.…”
Section: Introductionmentioning
confidence: 85%
“…Features of reported PR cases with oral lesions are summarized in Table 1. [7][8][9][10][11][12][13][14] Oral lesions appear to be more common in children than adults with PR. 5,15,16 In a study of 31 Caucasian children with PR, 11 (35%) had oropharyngeal lesions.…”
Section: Discussionmentioning
confidence: 99%